2013
DOI: 10.1016/j.taap.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Largazole, a class I histone deacetylase inhibitor, enhances TNF-α-induced ICAM-1 and VCAM-1 expression in rheumatoid arthritis synovial fibroblasts

Abstract: In the present study, we evaluated the effect of largazole (LAR), a marine-derived class I HDAC inhibitor, on tumor necrosis factor-α (TNF-α)-induced expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), and matrix metalloproteinase-2 (MMP-2) activity. LAR (1-5 μM) had no adverse effect on the viability of RA synovial fibroblasts. Among the different class I HDACs screened, LAR (1-5 μM) inhibited the constitutive expression of HDAC1 (0-30%). Surprisingly, LAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Furthermore, the authors showed that LAR modulated expression levels of HDAC1, HDAC5 and HDAC6 and indicated a role of HDAC6 in the LAR-induced changes of ICAM-1 and VCAM-1 expression levels. These results again point to the need for understanding the exact role of different HDAC enzymes in the RA pathogenesis in order to develop highly effective HDAC inhibitors for the treatment of RA [29]. Class I HDAC and HDAC6…”
Section: Histone Acetylationmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the authors showed that LAR modulated expression levels of HDAC1, HDAC5 and HDAC6 and indicated a role of HDAC6 in the LAR-induced changes of ICAM-1 and VCAM-1 expression levels. These results again point to the need for understanding the exact role of different HDAC enzymes in the RA pathogenesis in order to develop highly effective HDAC inhibitors for the treatment of RA [29]. Class I HDAC and HDAC6…”
Section: Histone Acetylationmentioning
confidence: 91%
“…Different HDAC inhibitors (Table 1), which mostly target several members of HDAC, were described to have beneficial effects in vitro and in vivo in RA [17,[25][26][27][28][29][30][31]. However, many of the observed effects of HDAC inhibitors were shown to be chromatin-independent and nonepigenetic (reviewed in [17]).…”
Section: Histone Acetylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both are implicated in RA pathology through their angiogenic and proliferative effects in inflamed synovium [44][45][46][47]. The infiltration and retention of inflammatory cells in RA synovium is facilitated by upregulation of VCAM-1 on endothelial cells and synovial fibroblasts in this tissue [48]. VCAM-1 was reduced in DTHA paws following anti-C5aR treatment, and as C5aR is expressed on endothelial cells and synovial fibroblasts [7] this reduction in VCAM-1 could represent a direct effect of anti-C5aR treatment on these cells.…”
Section: Discussionmentioning
confidence: 99%